2020
DOI: 10.3389/fphys.2020.615503
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Adipose Tissue as an Indication, Contributor to, and Therapeutic Target for Atherosclerosis

Abstract: Perivascular adipose tissue (PVAT) has been identified to have significant endocrine and paracrine functions, such as releasing bioactive adipokines, cytokines, and chemokines, rather than a non-physiological structural tissue. Considering the contiguity with the vascular wall, PVAT could play a crucial role in the pathogenic microenvironment of atherosclerosis. Growing clinical evidence has shown an association between PVAT and atherosclerosis. Moreover, based on computed tomography, the fat attenuation index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 114 publications
0
12
0
2
Order By: Relevance
“…Based on these studies, it can be concluded that under physiological conditions, PVAT possesses anti-inflammatory characteristics and inhibits the development of atherosclerosis. By contrast, under pathological conditions, such as obesity and diabetes, PVAT becomes dysfunctional and secrets pro-inflammatory adipokines that induce endothelial dysfunction and inflammatory cell infiltration, thus contributing to atherosclerosis ( 9 , 10 ). In this study, we focus on the association between healthy PVAT and macrophage foam cell formation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, it can be concluded that under physiological conditions, PVAT possesses anti-inflammatory characteristics and inhibits the development of atherosclerosis. By contrast, under pathological conditions, such as obesity and diabetes, PVAT becomes dysfunctional and secrets pro-inflammatory adipokines that induce endothelial dysfunction and inflammatory cell infiltration, thus contributing to atherosclerosis ( 9 , 10 ). In this study, we focus on the association between healthy PVAT and macrophage foam cell formation.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is caused by the accumulation of lipidrich macrophages in the subendothelial region of the vascular system. Macrophage accumulation in the subendothelial area of the arterial wall, and the lipid-rich cells promote an inflammatory response and leads to a variety of fatal pathological consequences [40][41][42]. Ferroptosis has been connected to a range of cardiovascular diseases, including heart failure, ischemia-reperfusion injury, and adriamycin cardiotoxicity [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between carotid artery disease and CSVD has been gradually revealed [ 13 15 ], the pathophysiologic mechanisms underlying the relationship between pericarotid fat and CSVD have not been fully established. Increasing studies have identified that perivascular fat has endocrine and paracrine functions, and the pathophysiological characteristics seem to be distinct in different anatomical locations and metabolic statuses [ 7 , 8 , 16 ].…”
Section: Discussionmentioning
confidence: 99%